2021
DOI: 10.1186/s13063-021-05678-8
|View full text |Cite
|
Sign up to set email alerts
|

Gas embolism under standard versus low pneumoperitoneum pressure during laparoscopic liver resection (GASES): study protocol for a randomized controlled trial

Abstract: Background Gas embolism induced by CO2 pneumoperitoneum is commonly identified as a risk factor for morbidity, especially cardiopulmonary morbidity, after laparoscopic liver resection (LLR) in adults. Increasing pneumoperitoneum pressure (PP) contributes to gas accumulation following laparoscopy. However, few studies have examined the effects of PP in the context of LLR. In LLR, the PP-central venous pressure (CVP) gradient is increased due to hepatic vein rupture, hepatic sinusoid exposure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Therefore, many hepatobiliary surgeons use intra-abdominal pressure rates of 10–14 mmHg to control back bleedings from hepatic veins during parenchymal transection, whereas other hepatobiliary surgeons reported pressure rates of 16–20 mmHg without safety issues [ 30 , 40 , 41 ]. However, a definitive consensus on which pressure to be used is not available due to the lack of prospective clinical trials [ 30 , 42 ]. In our study, none of the patients had gas embolism using a pneumoperitoneum rate up to 18 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many hepatobiliary surgeons use intra-abdominal pressure rates of 10–14 mmHg to control back bleedings from hepatic veins during parenchymal transection, whereas other hepatobiliary surgeons reported pressure rates of 16–20 mmHg without safety issues [ 30 , 40 , 41 ]. However, a definitive consensus on which pressure to be used is not available due to the lack of prospective clinical trials [ 30 , 42 ]. In our study, none of the patients had gas embolism using a pneumoperitoneum rate up to 18 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…According to the reported literature, the incidence of severe CO 2 embolism was less than 1%, but the mortality rate could reach 28% ( 7 ). However, it has also been shown that the overall incidence of intraoperative venous gas embolization was 38% and 69% in laparoscopic radical prostatectomy and cholecystectomy, respectively ( 8 ). One obvious mechanism of gas entering the vascular system is the open connection of the vein to the environment when the venous pressure is lower than the ambient pressure.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol will follow the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) reporting guidelines, which are reported in the SPIRIT checklist. 17 …”
Section: Methods and Analysismentioning
confidence: 99%